Evaluation of Community-Based Policy, Systems, and Environment Interventions Targeting the Vending Machines. Issue 3 (July 2017) - Garcia, Kristen M.; Garney, Whitney R.; Primm, Kristin M.; McLeroy, Kenneth R.
Abstract : The American Heart Association conducted policy, systems, and environmental (PSE) focused interventions to increase healthy vending in 8 communities. PSE interventions were assessed using the Nutrition Environment Measures Survey Vending Assessment to see changes in the food environment. Baseline and follow-up assessments were conducted with 3 settings and a total of 19 machines. PSE changes resulted in increased availability of healthy options and decreased unhealthy options. Implementation of PSE interventions targeting the food environment can be an effective method of providing increased access to healthy foods and beverages with the goal of increasing consumption to decrease chronic diseases.